FROM INBORN ERRORS OF IMMUNITY TO LYMPHOMA – A HEMATOLOGIST’S POINT OF VIEW OD UROĐENIH GREŠAKA IMUNITETA DO LIMFOMA – PERSPEKTIVA HEMATOLOGA - Goran MARJANOVIĆ; Tanja Dzopalic; Milos Kostic; Milan Lazarevic; Zlate Stojanovski; Branka Bonaci Nikolic (My University, 2022)
After infections, malignancies, lymphomas especially, are the second most frequent cause of death in patients with inborn errors of immunity. Factors predetermining the appearance and aggressiveness of lymphomas include gene defects, defects of immune surveillance and regulation as well as infections with oncogenic viruses. Aggressive non-Hodgkin lymphomas, mostly diffuse large B-cell and Bukit subtypes are predominant in deoxyribonucleic acid repair defects, while Hodgkin lymphoma becomes equally present in patients with defects of immune regulation. Marginal zone and mucosa-associated lymphoid tissue lymphomas, appear to be frequent in defects of antibody production, especially in patients with common variable immune deficiency. The prevalence of Epstein-Barr virus may vary within entities, but there is no entity without at least a few cases of lymphoma and Epstein-Barr virus co-infection. Standard treatment of lymphomas associated with deoxyribonucleic acid repair defects and severe combined deficiencies, is stem cell transplantation. Lymphomas in inborn errors of immunity with a less severe clinical presentation, should be treated with immunochemotherapy and monoclonal antibodies (Brentuximab, Rituximab) wherever feasible. There is no data about the usefulness of checkpoint inhibitors, bi-specific antibodies and T-cells with chimeric antigen receptor. Allogeneic stem cell transplantation represents a major indication for treatment of relapse/refractory lymphomas in any inborn error of immunity. Potential benefit of therapy with Chimeric antigen receptor Natural-killer cells in lymphomas associated with inborn errors of immunity, remains to be seen in future studies. Key words: Immune System Diseases; Metabolism, Inborn Errors; Lymphoma; Hodgkin Disease; Lymphoma, Non-Hodgkin; Therapeutics
Keywords: primary immunodeficiency; Non Hodgkin Lymphoma; immune system